26 Weight loss in obesity causes a reduction in the creatine kinase rate constant. (May 2018) - Rayner, Jennifer J; Clarke, William T; Peterzan, Mark A; Neubauer, Stefan; Rodgers, Christopher; Rider, Oliver J
Abstract : Introduction: Obesity is associated with diminished myocardial energetic stores, as determined by PCr/ATP, and this is restored with weight loss. We have previously demonstrated that the creatine kinase rate constant ( k f CK ) is elevated in obesity, which may represent a compensatory mechanism preserving ATP delivery. We hypothesised that intentional weight loss would reduce the requirement for increased enzyme activity, and hence k f CK would fall. Methods: 31 obese individuals (53±13 years, 11 male, BMI 37±5 kg/m -2 ) underwent comprehensive metabolic phenotyping including MR (3 T, Siemens) for abdominal, hepatic and myocardial fat, and cardiac MR for structure and function. Triple Repetition time Saturation Transfer (TRiST) 31 P magnetic resonance spectroscopy was used to measure k f CK . Participants then underwent repeat testing following a dietary weight loss intervention. Results: Mean BMI in the cohort fell from 37±5 kg/m -2 to 33±6 kg/m -2 (p<0.001), with 22 volunteers losing more than 10% body fat (mean −20±15%, p=0.004) and only 2 gaining weight. LV end-diastolic volume and mass fell (from 158±36 ml to 153±35 ml (p<0.001) and 115±31 g to 105±26 g (p=0.006) respectively. k f CK fell from 0.17±0.05s -1 to 0.12±0.05s -1 (p=0.001), a change which correlated with change in both fat mass (r=0.623, p=0.006), and visceral fat volume (r=0.565, p=0.010). Conclusion: We demonstrate that dietary weight loss in an obese population is associated with a fall in k f CK . It has previously been shown that weight loss in this population is associated with an increase in the PCr/ATP ratio. Our findings may reflect a recalibration of the required k f CK in the context of replenished substrate pool (i.e. higher PCr levels). The impact of weight loss in diseases with more profound myocardial energetic deficit must be investigated to establish its safety.